UTILIZATION OF THE TYPER SHARK DELUXE APPLICATION TO INCREASE INTEREST AND QUALITY OF LEARNING TYPING GRADE IX STUDENTS OF INTEGRATED JUNIOR HIGH SCHOOL SCHOLARS HUMAN BEINGS NURUL HUDA PAOWAN - Zahro, Nuri Nadiatuz; Sahwari, Sahwari; Astindari, Tri (STKIP PGRI Situbondo, 2024)
Improving the quality of education must be supported by improving the quality of learning. Improving the quality of education must be supported by improving the quality of learning. There are various efforts to enhance students' learning quality, multiple efforts, among others, by arousing interest in learning. This study aims to see the extracurricular relationship of learning to type using the Typer Shark Deluxe application to increase the interest and quality of typing learning of Class IX Integrated Junior High School Cendekia Insani Nurul Huda Paowan students. This research uses a qualitative descriptive approach, with the researcher's position as the main instrument (key), while sampling data sources is carried out with Purposive and Snowball techniques. Data collection techniques use triangulation (combined) methods; data analysis is inductive/qualitative, and qualitative research results emphasize meaning rather than generalization. Data analysis techniques use an interactive data analysis model, which includes four components: data collection, data reduction, data presentation, and conclusion drawing. Judging from the results of the data obtained, using the Typer Shark Deluxe application is very useful for increasing the interest and quality of learning to type class IX students of Integrated Junior High School Cendekia Insani Paowan.